Bridging the Gap between Genes and Language Deficits in Schizophrenia: An Oscillopathic Approach - Murphy, Elliot; Benítez-Burraco, Antonio (Frontiers in Human Neuroscience, 2016)
Schizophrenia is characterised by marked language deficits, but it is not clear how these deficits arise from the alteration of genes related to the disease. The goal of this paper is to aid the bridging of the gap between genes and schizophrenia and, ultimately, give support to the view that the abnormal presentation of language in this condition is heavily rooted in the evolutionary processes that brought about modern language. To that end we will focus on how the schizophrenic brain processes language and, particularly, on its distinctive oscillatory profile during language processing. Additionally, we will show that candidate genes for schizophrenia are overrepresented among the set of genes that are believed to be important for the evolution of the human faculty of language. These genes crucially include (and are related to) genes involved in brain rhythmicity. We will claim that this translational effort and the links we uncover may help develop an understanding of language evolution, along with the aetiology of schizophrenia, its clinical/linguistic profile, and its high prevalence among modern populations.